Tuberous sclerosis complex and acute kidney injury in an adult female nigerian: a rare presentation and review of the literature. (2012)
Tuberous sclerosis complex (TSC) is a rare condition classically characterized by mental retardation, facial angiofibroma (adenoma sebaceum) and epilepsy. It is an autosomal dominant disorder with formation of harmatomas involving multiple organs such as the skin, central nervous system, kidneys, lungs, and heart. The renal manifestations of TSC include formation of angiolipoma, cyst formation and renal malignancies. The occurrence of renal failure is very rare in patients with tuberous sclerosis, though it is projected that more cases with renal impairment will be seen as a result of improved life expectancy arising from improving standard of neurology care services received by these patients. We report a case of 25year old female Nigerian with tuberous sclerosis complex and acute kidney injury precipitated by sepsis.